Fluid–structure interaction simulations of a wind turbine rotor in complex flows, validated through field experiments. Issue 12 (23rd March 2021) - Grinderslev, Christian; González Horcas, Sergio; Sørensen, Niels Nørmark
Abstract: Aeroelastic simulations of a 2.3 MW wind turbine rotor operating in different complex atmospheric flows are conducted using high fidelity fluid–structure interaction (FSI) simulations. Simpler blade element momentum (BEM) theory based simulations are likewise conducted for comparison, and measurements from field experiments are used for validation of the simulations. Good agreement is seen between simulated and measured forces. It is found that for complex flows, BEM‐based simulations predict similar forces as computational fluid dynamics (CFD)‐based FSI, however with some distinct discrepancies. Firstly, stall is predicted for a large part of the blade using BEM‐based aerodynamics, which are not seen in either FSI simulations or measurements in the case of a high shear. This leads to a more dynamic structural response for BEM‐based simulations than for FSI. For a highly yawed and sheared flow case, the BEM‐based simulations overpredict outboard forces for a significant part of the rotation. This emphasizes the need of validation of BEM‐based simulations through higher fidelity methods, when considering complex flows. Including flexibility in simulations shows only little impact on the considered rotor for both FSI‐ and BEM‐based simulations. In general, the loading of the blades increases slightly, and the rotor wake is almost identical for stiff and flexible FSI simulations.